Mechanochemical Synthesis of Fluorine-Containing Co-Doped Zeolitic Imidazolate Frameworks for Producing Electrocatalysts - Rautenberg, Max; Gernhard, Marius; Radnik, Jörg; Witt, Julia; Roth, Christina; Emmerling, Franziska (Frontiers in Chemistry, 2022)
CCatalysts derived from pyrolysis of metal organic frameworks (MOFs) are promising candidates to replace expensive and scarce platinum based electrocatalysts commonly used in polymer electrolyte membrane fuel cells (PEMFCs). MOFs contain ordered connections between metal centers and organic ligands. They can be pyrolyzed into metal- and nitrogen-doped carbons (MNCs), which show electrocatalytic activity towards the oxygen reduction reaction (ORR). Furthermore, metal free heteroatom-doped carbons, such as N-F-Cs, are known for being active as well. Thus, a carbon material with Co-N-F doping could possibly be even more promising as ORR electrocatalyst. Herein, we report the mechanochemical synthesis of two polymorphs of a zeolitic imidazole framework (ZIF), Co-doped zinc 2-trifluoromethyl-1H-imidazolate. Time-resolved in situ XRD studies of the mechanochemical formation revealed a direct conversion of starting materials to the products. Both polymorphs of the Co-doped CF3-ZIF-8 were pyrolyzed, yielding Co-N-F containing carbons, that are active towards electrochemical oxygen reduction reaction (ORR).